Population Pharmacokinetics of Cefoxitin Administered for Pediatric Cardiac Surgery Prophylaxis. Issue 7 (July 2020) - Ricci, Zaccaria; Benegni, Simona; Cies, Jeffrey J.; Marinari, Eleonora; Haiberger, Roberta; Garisto, Cristiana; Rizza, Alessandra; Giorni, Chiara; Di Chiara, Luca; Arpicco, Silvia; Muntoni, Elisabetta; Ferrari, Fiorenza; et al.
Abstract : Background: Available data about pharmacokinetics (PK) of antimicrobials administered as surgical prophylaxis to children undergoing cardiac surgery with cardiopulmonary bypass (CPB) showed that drug concentrations during CPB may be supra or subtherapeutic. The aim of this study was to determine the population PK and pharmacodynamic target attainment (PTA) of cefoxitin during pediatric CPB surgery. Methods: A prospective interventional study was conducted. Cefoxitin (40 mg/kg, up to max 1000 mg) was administered before skin incision. Blood samples were obtained in the operatory room throughout surgery. Population PK, PTA, and safety of cefoxitin were evaluated in neonates, infants, children <10 and >10 years old. Results: Forty patients were enrolled. Cefoxitin levels correlated with time from bolus administration ( r = −0.6, P = 0.0001) and, after 240 minutes from bolus, drug values below the target (8 mg/L) were shown. Cefoxitin concentrations were best described by a one-compartment model with first order elimination. A significant relationship was identified between body weight, age, body mass index, and serum creatinine on drug clearance and age, body weight, and body mass index on cefoxitin volume of distribution. The PTA for free drug concentration being above the minimum inhibitory concentration of 8 mg/L for at least 240 minutes was >90% in all age groups except in patients >10 years of age (PTA = 62%). Conclusions: Cefoxitin PK appears to be significantly influenced by CPB with generally reduced drug clearance. The PTA was adequately achieved in the majority of patients except in patients >10 years old or longer surgeries. Abstract : Supplemental Digital Content is available in the text.